The genera Polygonum and Bilderdykia (Polygonaceae) in southern Africa: morphology and taxonomic value of the ocrea and fruit - G. Germishuizen; P. J. Robbertse; P. D. F. Kok (Bothalia: African Biodiversity & Conservation, 1989)
The external morphology of the fruit and the ocrea of 16 taxa of Polygonum and Bilderdykia in southern Africa was studied.Fruits are either lenticular or trigonous. Six types of fruit surfaces were distinguished. Five types of ocreae were found, characterized by: a green undulating limb; a silvery hyaline sheath; a brown tubular sheath without terminal hairs; a terminal fringe of short cilia or setae; and a bristly hairy sheath fringed with long rigid setae.